PENERAPAN MEKANISME HAK JAWAB BERDASARKAN UNDANG-UNDANG NOMOR 40 TAHUN 1999 TENTANG PERS DALAM TINDAK PIDANA PENCEMARAN NAMA BAIK - Dianto Simanjuntak; Erdianto '; Dessy Artina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Implementation Mechanism of Right of Reply by Act No. 40 of 1999 on the Press and the application of the Criminal Code (the Code of Penal Code) is an issue in dispute resolution press specifically the crime of defamation. On the one hand look when problems occur between the press and the public or the press with laws such as the police, the legal consequences that should be accepted by the press is going to deal with the articles of defamation in the book of the law of criminal law (Criminal Code). Jurisprudence on